Analysis of the Ideal Concept of Corporate Responsibility in Environmental Crimes - Rhiti, Hyronimus (Universitas Ekasakti, 2023)
The problem with law enforcement for environmental crimes is that in prosecuting perpetrators of environmental crimes, the emphasis is still on the element of error. The implication of this problem is that it is difficult to prove environmental crimes, considering that the perpetrators of environmental crimes are not only people (natuurlijk person) but also include corporations (recht person). Legislation regarding the environment, especially Law Number 32 of 2009, has determined responsibility for perpetrators of environmental crimes using the strict liability theory. This article will discuss the implementation of strict liability theory to find the ideal concept for dealing with environmental crime. The method used in writing this article is normative legal research with a statutory approach. The results of this research are the ideal concept of corporate responsibility for the occurrence of environmental crimes in the form of payment of compensation (civil) and punishment of perpetrators (criminal sanction).